Practical synthesis of 1,3-benzoazaphosphole analogues - Yuki Yamamoto; Soichiro Mita; Yuki Sato; Kentaro Yano; Akiya Ogawa (Frontiers in Chemistry, 2023)
Despite the promising pharmacological activity and material properties of five-membered heterocyclic compounds containing phosphorus and nitrogen, synthetic examples of them have been rather limited due to the instability of phosphorus toward air and water. In this study, 1,3-benzoazaphosphol analogues were selected as target molecules, and various synthetic routes were examined to establish a fundamental technology for the introduction of phosphorus groups into aromatic rings and formation of five-membered rings containing phosphorus and nitrogen by cyclization. As a result, we found that 2-aminophenyl(phenyl)phosphine is an extremely promising synthetic intermediate with high stability and easy handling. Furthermore, 2-methyl-3-phenyl-2,3-dihydro-1H-benzo[d][1,3]azaphosphole and 3-phenyl-2,3-dihydro-1H-benzo[d][1,3]azaphosphole-2-thione as synthetically useful 1,3-benzoazaphosphol analogues were successfully synthesized by using 2-aminophenyl(phenyl)phosphine as a key intermediate.